QTL Analysis of Shoot Ureide and Nitrogen Concentrations in Soybean [Glycine max (L.) Merr.]. Issue 6 (1st November 2013) - Hwang, Sadal; King, C. Andy; Davies, Marilynn K.; Ray, Jeffery D.; Cregan, Perry B.; Purcell, Larry C.
ABSTRACT: Nitrogen (N) fixation in soybean [ Glycine max (L.) Merr.] is more sensitive to drought than photosynthesis, and high concentrations of shoot ureide and N are associated with sensitivity of N2 fixation to drought. Genotypic differences in ureide and N concentration were evaluated using a mapping population of 97 recombinant inbred lines derived from a cross between 'KS4895' and 'Jackson'. For three irrigated environments, broad‐sense heritability for ureide and N concentration was 0.73 and 0.59, respectively. Under irrigated conditions, five quantitative trait loci (QTLs) for ureide concentration were identified using composite interval mapping (CIM). Multiple interval mapping (MIM) identified two QTLs with locations similar to those identified with CIM. Four QTLs for N concentration were detected using CIM, and one QTL was identified with MIM with a similar position as that identified with CIM. A QTL on Gm13 for shoot ureide and N appeared to be pleiotropic. In the drought environment, two QTLs were identified using CIM for both shoot ureide and N; a QTL for ureide concentration on Gm19 mapped to the same position as a ureide QTL under irrigated conditions, but the additive effect was opposite in sign. A search for metabolic genes in QTL regions predicted for the pleiotropic effect of N and ureide (Gm13, carbonic anhydrase) and for ureide (Gm19, inosine–uridine nucleoside hydrolase). These QTLs may be useful in selecting lines drought tolerant for N2 fixation.